084 Anticipating the unexpected; a well-designed checklist will save lives, prevent complications and improve safety. (December 2018) - Lock, E; Roberts, C
Abstract : Introduction: The Children's Acute Transport Service (CATS) is a stand-alone paediatric critical care service that performs approximately 1200 retrievals a year in the North Thames region. A significant focus of critical care transport is anticipating the unexpected. Through the use of a well thought out checklist and appropriate team collaboration, the checklist review aimed to update and optimise this process to improve patient safety during critical care transport. Checklists by themselves do not improve care. 1 They are employed as a tool to support practice among staff committed to making them work. However, a well-designed checklist may potentially save lives, prevent complications, and improve safety. Methods: Through the implementation of a PDSA cycle, the original checklist was reviewed, and objectives were made based on service needs. The plan was implemented. The results obtained were analysed and improvements were implemented. The new checklist was implemented and audited further, providing an opportunity for all users to comment. Results: Through brainstorm, drafting and team exchanges the checklist was reformatted. The checklist was made in a more logical order, improving the relevance and ease of use. The non-clinical emergency tool was added to encourage departure team briefing. Safety reminders were added. Discussion and conclusion: The new checklist was implemented into practice. Refreshed team huddles during 3 stages of each retrieval were launched; this ensured systematic demonstration of equipment available, a summary of the situation, and team plans for unforeseen events. CATS Staff were educated regarding the power of the checklist and the importance of effective use. Ultimately the newly improved checklist is safer, more effective and more efficient. Reference: Alspach J. The checklist: Recognise limits but harness its power. Critical Care Nurse2017;37(5):12–17.